Extending the age range for breast screening in England: pilot study to assess the feasibility and acceptability of randomization. - Moser, K; Sellars, S; Wheaton, M; Cooke, J; Duncan, A; Maxwell, A; Michell, M; Wilson, M; Beral, V; Peto, R; Richards, M; Patnick, J (2011)
To assess the feasibility and acceptability of randomizing the phased introduction of the extension of the invited age range in the National Health Service (NHS) Breast Screening Programme in England from 50-70 to 47-73 years.